Elucidating Quadruplication Event of PHO1 Gene: A Key Regulator of Plant Phosphate Translocation in Brassica rapa - Dahlia Shahbuddin; Rosazlina Rusly; Ahmad Naqib Shuid; Ahmad Bukhary Ahmad Khair (Horticulturae, 2023)
In response to Pi deprivation, phosphate 1 (PHO1) is a significant regulator at trans-eQTL hotspots in Brassica rapa. Brassica rapa short-read sequencing data analysis revealed four PHO1 paralog genes, PHO1_A, PHO1_B, PHO1_C, and PHO1_D, placed in tandem with very high sequence similarity. However, based on short-read genomic sequence data, only three transcripts are accessible. Five bacterial artificial chromosomes (BACs) can be sequenced using a long-read sequencer, which improves de novo assembly and identifies structural variants. The PHO1 gene’s quadruplicating tandem positions in the genomic sequence were confirmed by an analysis of long-read data. Transcript analysis identified only three groups of PHO1 paralogs (ortholog AT1G14040 in Arabidopsis), i.e., PHO1_A, PHO1_B, and PHO1_D, expressed in B. rapa leaf tissues under Pi deficiency. PHO1_A, with transcript ID XM_009150437.2, has five different splice variants found. These splice variants’ truncated proteins demonstrated PHO1_A’s function in P control as opposed to protein encoding.